Attentional modulation of perceptual grouping in human visual cortex: functional MRI studies. - Han, S; Jiang, Y; Mao, L; Humphreys, G; Gu, H (2005)
When presented with a complex visual scene, our visual system has to organize the discrete entities present into useful perceptual units. The current work investigated the neural substrates of perceptual grouping defined by Gestalt laws of proximity and similarity of shape, and whether the neural substrates underlying perceptual grouping are modulated by task relevance and spatial attention. In visual discrimination tasks, subjects identified the orientations of perceptual groups formed by proximity or similarity of local elements or alternatively identified colors of either dots around the grouped stimuli or the fixation cross. Using functional magnetic resonance imaging (fMRI), we identified that the calcarine cortex was involved in proximity grouping but not in the grouping process defined by similarity of shape. Moreover, we showed evidence that the neural correlates of proximity grouping in the calcarine cortex were weakened when the elements were of low task relevance and fell outside an attended area of field. The findings reveal the neural basis for basic grouping operations, as well as illustrating how attention and proximity grouping interact in human visual cortex.